Implementation of the spectrum of ramcode design curves of unsaturated subgrade soils in the design of flexible pavements - Inga López, Hainer Josué (2022)
The design process for a pavement structure assumes that the subgrade will saturate at some point during the service life, however, the saturation of the subgrade depends on the conditions depending on the region in which it is located. Therefore, it is necessary to study design conditions for partially saturated subgrade. The present research aims to implement the spectrum of RAMCODES design curves for unsaturated subgrade soils, applied to the design of flexible pavements under environmental and traffic conditions associated with the Oyon-Ambo highway. To construct the RAMCODES design curves, CBR tests were performed by varying compaction energies and moisture contents.  Likewise, using the OriginPro 2019 program, the curves were obtained and a mathematical model was used to predict the variation of the degree of saturation in the subgrade over time. Subsequently, the seasonal CBR were obtained and correlated to obtain the resilient moduli. Finally, two flexible pavement structure designs were carried out, one using the traditional subgrade characterization methodology and the other according to the proposed methodology. From the results obtained, it is interpreted that the consideration of the unsaturated behavior of the subgrade optimizes the pavement design since the bearing capacity of the subgrade is increased by 28.8%, which means that the thickness of the subbase layer is reduced by 25%.